2017
DOI: 10.22146/jsv.29298
|View full text |Cite
|
Sign up to set email alerts
|

Morfologi Hemipenis Biawak Air (Varanus salvator bivittatus)

Abstract: Varanus salvator bivittatus has a pair of hemipenes, which is macroscopic anatomically like the copulatory organ in other amniotes, cylindrical-shaped (truncus) with quite flexible, and it located on the base of the caudal tail of the cloaca. However, information about the microscopic anatomy of hemipenes of this animal is scientifically unpublicized. Therefore, the aim of this research is to study the microscopic anatomy of hemipenes of male Varanus salvator bivittatus. The animals were sacrificed by exsangui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…The macroscopic findings show the absence of spicules, which have been described in other Boidae specimens, and of spermatic sulcus spermaticus, also described in different species of snakes and lizards (Branch, 1981;Karim, 1998;Mahfud et al, 2017;Porto et al, 2013;Zaher & Prudente, 2003). In addition, the hemipenis structural organization, showing the m. retractor penis magnus with internal and external cavernous bodies, proved to be similar among the species studied in this study and observed in Crotalus d. terrificus (Porto et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…The macroscopic findings show the absence of spicules, which have been described in other Boidae specimens, and of spermatic sulcus spermaticus, also described in different species of snakes and lizards (Branch, 1981;Karim, 1998;Mahfud et al, 2017;Porto et al, 2013;Zaher & Prudente, 2003). In addition, the hemipenis structural organization, showing the m. retractor penis magnus with internal and external cavernous bodies, proved to be similar among the species studied in this study and observed in Crotalus d. terrificus (Porto et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…Inside epididymis, there was aligning of pseudostratified columnar epithelial cells with thin stereocilia on top, and in the lumen epididymis were spermatozoa shaped incomplete normal morphology. Histology of the epididymis of Tokay gecko was not much different with Varanus salvator (Mahfud et al, 2017).…”
Section: Male Reproductive Microanatomymentioning
confidence: 77%
“…Glandula bulbourethralis di sebagian besar hewan pengerat terdiri dari sel epitel kuboid selapis (Sirigu et al, 1993) dan sel epitel silindri selapis pada babi (Badia et al, 2006), serta ditemukan sel epitel banyak lapis semu pada manusia (Chughtai et al, 2005). Selsel epitel bersilia, hanya ditemukan pada saluran-saluran sperma, seperti ductus deferens dan ductus epididymidis pada biawak air (Mahfud et al, 2016). Pada hampir semua spesies eutherian, glandula bulbourethralis adalah kelenjar tubuloalveoler yang lapaisi oleh kapsul berupa jaringan ikat padat yang darinya sehingga membagi kelenjar menjadi lobus dan lobulus (Adebayo et al, 2014).…”
Section: Hasil Dan Pembahasanunclassified